ANALISIS KESUBURAN TANAH DENGAN INDIKATOR MIKROORGANISME TANAH PADA BERBAGAI SISTEM PENGGUNAAN LAHAN DI PLATEAU DIENG - - Susilawati; Eriandra Budhisurya; R. C. W. Anggono; Bistok Hasiholan Simanjuntak (Agric, 2013)
Dieng is a plateau region, with an altitude about ± 2095 meters above sea level. Dieng Plateau is unique land because that has low air temperature and soil dominated Andisol and has various land slope from 0 percent until >40 percent. Therefore, Dieng Plateau is ideal land for horticultural cultivations. The serious problem in Dieng Plateau was conducted intensively conversion the forest area to the various land use system, to example for land potatoes cultivation, settlements and tourist activity. These conditions increasing hazard for the rate soil erosion. High soil erosion rate will decrease the soil fertility.This study aims to determine the level of soil fertility with indicators of soil microorganisms in a various of land use, given the high levels of soil erosion. The layout design of the research used is a Randomized Complete Block Design (RCBD). Analysis of the data used is Analysist of Variance – ANOVA (F test), Honestly Significant Analysis (5%) and Stepwise Regressiont. To determination the number of carbon biomass of microorganisms is applied with fumigation-extraction method. Fordetermination of total soil microorganisms using NA media, where as the determination of soil respiration using Verstraete method.The results showed that the land is sloping physiography (tourist land and residential) have higher fertility than high physiographic area, as a result of soil erosion. Different case for protected forests, although a high physiographic land, forests have higher fertility than the land potatos cultivation. Forest area are still natural, and its has a vegetation litter and diversity of vegetations, therefor the forest area has good barrier water runoff that carries organik material and soil salts.